AKUNTANSI PENJUALAN BAHAN KEBUTUHAN POKOK DI SWALAYAN CV.BERKAT ANUGERAHBARONG TONGKOK - DAMAYANTI ,Elfreda Aplonia Lau, Titin Ruliana, DAMAYANTI , Elfreda Aplonia Lau, (EKONOMIA, 2016)
The purpose and usefulness are expected from this study as follows:To know the amount of sales obtained in Supermarkets CV. Berkat Anugerah Barong Tongkok in 2013 and 2014. To know the amount of net income earned in Supermarkets CV. Berkat Anugerah Barong Tongkok in 2013 and 2014. Based on the background described above, the main problem of this study is as follows: